CD4+ and CD8+ cell counts are significantly correlated with absolute lymphocyte count in hospitalized COVID-19 patients: a retrospective study - Liana, Phey; Samosir, Aprilia Paskah; Sari, Nurmalia Purnama; Andriani, Raden Ayu Linda; Verdiansah, Verdiansah; Hidayatullah, Hidayatullah; Ahmad, Zen; Umar, Tungki Pratama (PeerJ, 2023)
Background Coronavirus disease 2019 (COVID-19) is a contagious respiratory illness that was declared a pandemic in March 2020. Lymphopenia is one of the specific laboratory results disturbance in COVID-19 patients. Such findings are frequently associated with substantial changes in T-cell counts, particularly CD4+ and CD8+ T-cells. This study aimed to examine the correlation between CD4+ and CD8+ cell counts and absolute lymphocyte count (ALC) in COVID-19 patients and analyze its difference based on the COVID-19 patients’ severity. Methods From March 2022 to May 2022, we conducted a retrospective cohort study using medical records and laboratory data from patients diagnosed with COVID-19 at our hospital who met the inclusion and exclusion criteria. The total sampling method was used to recruit study participants. We conducted bivariate analysis, which consisted of correlation and comparative analysis. Results Thirty-five patients met the inclusion and exclusion criteria and were divided into two severity groups (mild-moderate and severe-critical). The findings of this study revealed a significant correlation between CD4+ cell count and ALC on admission (r = 0.69, p < 0.001) and the tenth day of onset (r = 0.559, p < 0.001). Similarly, there was a correlation between CD8+ and ALC at admission (r = 0.543, p = 0.001) and on the tenth day of onset (r = 0.532, p = 0.001). Individuals with severe-critical illness had lower ALC, CD4+, and CD8+ cell counts than those with mild-moderate illness. Conclusion According to the findings of this study, there is a correlation between CD4+ and CD8+ cell counts and ALC in COVID-19 patients. All lymphocyte subsets also showed a lower value in severe forms of the disease.
Keywords: COVID-19; Hematology; Laboratory; Lymphocyte